0179 Low-Amplitude tDCS Does Not Affect Threat Detection Performance Under Sleep Loss. (27th April 2018) - Gill, H A; Bryant, N B; Mertens, N A; Jones, A P; Robert, B; Clark, V; Pilly, P K
Abstract: Introduction: Cognitive functioning declines under sleep loss. Studies show 2.0 mA of transcranial direct current stimulation (tDCS) applied to the prefrontal cortex improves cognitive performance on a visuospatial threat detection task, and a similar montage rescues sleep-deprived performance decline. We sought to test whether 1.0 mA of tDCS is sufficient to improve threat detection performance under sleep loss. Methods: Twenty-one volunteers slept overnight in the lab undergoing polysomnographic recording. The following afternoon they completed a threat detection task, involving baseline, training, and immediate tests, where they learned to identify threats hidden in complex images. During training, participants saw short video clips displaying the consequences of their choices, and received either active (1.0 mA) or sham (0.1 mA) stimulation over F8 with the return on the arm. Learning was calculated as the difference between post-training immediate test and pre-training baseline scores. The amount of sleep each subject received was calculated by the difference between time in bed and wake minus awakenings Results: Results showed no significance interactions among sleep amount, condition, or learning on the threat detection task (p=0.5479). Post-sleep threat detection learning was not influenced by either condition type (p= 0.868) or total sleep amount (p= 0.546). Conclusion: Previous research shows 2.0 mA to be effective in rescuing cognitive performance after deficient sleep, 1.0 mA was not sufficient in the present study. Perhaps the threat detection task is not sensitive to the effects of sleep loss like other, less engaging psychomotor vigilance tasks. Another potential factor was that a different stimulation device was used in the current study compared to previous research. Future research should assess whether 1.0 mA affects cognitive performance on tasks that are more sensitive to the effects of sleep deficit. Support (If Any): This material is based upon work supported by the DARPA and the Army Research Office under Contract No. W911NF-16-C-0018. Any opinions, findings, and conclusions or recommendations expressed in this material are those of the author(s) and do not necessarily reflect the views of the DARPA or the Army Research Office.